Interleaved High Step-up DC-DC Converter with Diode-Capacitor Multiplier Cell and Ripple-Free Input Current - Jalalian Ebrahimi, Mostafa; Houshmand Viki, Abbas (Bulletin of Electrical Engineering and Informatics, 2015)
In this paper interleaving and switched-capacitor techniques are used to introduce a high step-up DC-DC converter for renewable energy systems application. The proposed converter delivers high voltage gain without utilizing transformer or excessive duty cycle and features ripple-free input current which results in lower conduction losses and decreased electromagnetic interference (EMI). Lower output capacitance is another advantage of proposed converter, leading to smaller size and lower cost. Furthermore lower voltage stress on switches allows the utilization of switches with low resistance. Simulation results verify the performance of suggested converter.